The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1108/cg-03-2020-0106
|View full text |Cite
|
Sign up to set email alerts
|

Does the market for corporate control influence executive risk-taking incentives? Evidence from takeover vulnerability

Abstract: Purpose This study aims to investigate the role of the market for corporate control as an external governance mechanism and its effect on executive risk-taking incentives. Managers tend to be risk-averse as they are more exposed to idiosyncratic risk, resulting in sub-optimal risk-taking that does not maximize shareholders’ wealth. The takeover market alleviates this problem, inducing managers to take more risk. Therefore, risk-taking incentives inside the firm are less powerful when the outside takeover marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
65
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 39 publications
(67 citation statements)
references
References 65 publications
(108 reference statements)
2
65
0
Order By: Relevance
“…Second, our study extends the literature on managerial risk-taking incentives as we demonstrate that board gender diversity is one of the significant determinants of risk-taking incentives [9][10][11][12][13][14][15][16]. Our results robustly support the arguments underlying the laws and regulations that promote gender diversity.…”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…Second, our study extends the literature on managerial risk-taking incentives as we demonstrate that board gender diversity is one of the significant determinants of risk-taking incentives [9][10][11][12][13][14][15][16]. Our results robustly support the arguments underlying the laws and regulations that promote gender diversity.…”
Section: Introductionsupporting
confidence: 78%
“…Stock options are thus provided to induce managers to engage in more risk-taking. The importance of this branch of research is demonstrated by the existence of a large literature on managerial risk-taking incentives [9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Second, our study extends the literature on managerial risk-taking incentives as we demonstrate that board gender diversity is one of the significant determinants of risk-taking incentives [ 9 16 ]. Our results robustly support the arguments underlying the laws and regulations that promote gender diversity.…”
Section: Introductionsupporting
confidence: 64%
“…Stock options are thus provided to induce managers to engage in more risk-taking. The importance of this branch of research is demonstrated by the existence of a large literature on managerial risk-taking incentives [ 9 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The risk premium assumption of the agency theory proposes that the risk premium should be included in the compensation to adjust it to the systematic and unsystematic risks of the firm, especially for the firms that operate in riskier environments. Risk premium will encourage the risk-taking behavior of executives and help firms hire less risk-averse managers (Bolton et al, 2015;Ongsakul et al, 2020). Dee et al (2005) stated that all firms want to hire less risk-averse managers and they compete among themselves for their services, so agents have to be compensated for bearing additional risk, resulting in higher total compensation.…”
Section: Introductionmentioning
confidence: 99%